The E3 Ligase PIAS1 Regulates p53 Sumoylation to Control Stress-Induced Apoptosis of Lens Epithelial Cells Through the Proapoptotic Regulator Bax - Nie, Qian; Chen, Huimin; Zou, Ming; Wang, Ling; Hou, Min; Xiang, Jia-Wen; Luo, Zhongwen; Gong, Xiao-Dong; Fu, Jia-Ling; Wang, Yan; Zheng, Shu-Yu; Xiao, Yuan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Protein sumoylation is one of the most important post-translational modifications regulating many biological processes (Flotho A & Melchior F. 2013. Ann Rev. Biochem. 82:357-85). Our previous studies have shown that sumoylation plays fundamental role in regulating lens differentiation (Yan et al. 2010. PNAS, 107(49):21034-9.; Gong et al., 2014. PNAS. 111(15):5574-9.). Whether sumoylation is implicated in lens pathogenesis remains elusive. Here, we present evidence to show that the protein inhibitor of activated STAT-1 (PIAS1), a E3 ligase for sumoylation is implicated in regulating stress-induced lens pathogenesis. During oxidative stress-induced cataractogenesis, expression of PIAS1 is significantly altered at both mRNA and protein levels. Upregulation and overexpression of exogenous PIAS1 significantly enhances stress-induced apoptosis. In contrast, silence of PIAS1 with CRISPR/Cas9 technology attenuates stress-induced apoptosis. Mechanistically, different from other cells, PIAS1 has little effect to activate JNK but upregulates Bax, a major proapoptotic regulator. Moreover, Bax upregulation is derived from the enhanced transcription activity of the upstream transcription factor, p53. As revealed previously in other cells by different laboratories, our data also demonstrate that PIAS1 promotes SUMO1-conjugation of p53 at K386 residue in lens epithelial cells and thus enhances p53 transcription activity to promote Bax upregulation. Silence of Bax expression largely abrogates PIAS1-mediated enhancement of stress-induced apoptosis. Thus, our results demonstrated that PIAS1 promotes oxidative-stress induced apoptosis through positive control of p53, which specifically upregulates expression of the downstream proapoptotic regulator, Bax. As a result, PIAS1-promoted apoptosis induced by oxidative stress is implicated in lens pathogenesis.